Apakah Penggunaan Teknologi Informasi Dan Kepemimpinan Transformasional Dapat Meningkatkan Perrforma Karyawan? - Sjahruddin, Herman; Gumanty, Rachmat; Anto, Ahmad; Mochtar, Hasyim (Politeknik Negeri Ambon, 2024)
Employee performance is an achievement achieved by employees when carrying out responsibilities in an agency as an effort to achieve the end of a company that is considered legal in the eyes of the law. The purpose of this finding is to analyze the effect of implementing information technology and transformational leadership on employee performance at PT Bank KB Bukopin Makassar Branch. The number of samples was 159 respondents and 72 data were not used because they did not match the criteria in the study. The results of regression testing show that the use of good information technology will improve employee performance. This condition is different from transformational leadership which shows that transformational leadership does not contribute to employee performance. Keywords: Banking, information technology, transformational leadership, performance